Knowledge of and Attitudes Towards Standard Care in Patients with COPD - Zimmermann M; von Plessen CM; Kroppen D; Stanzel SB; Berger M; Wollsching-Strobel M; Feldmeyer F; Kellner C; Mathes T; Windisch W; Majorski DS (International Journal of COPD)
Maximilian Zimmermann,1 Charlotte Maria von Plessen,2 Doreen Kroppen,1 Sarah B Stanzel,1 Melanie Berger,1 Maximilian Wollsching-Strobel,1 F Feldmeyer,3 Cornelius Kellner,3 Tim Mathes,4 Wolfram Windisch,1,2 Daniel S Majorski1 1Department of Pneumology, Cologne Merheim Hospital Kliniken der Stadt Köln gGmbH, University Hospital of Witten/Herdecke University, Lung Clinic, Cologne, Germany; 2Faculty of Health, Witten/Herdecke University, Witten, Germany; 3Gemeinschaftspraxis Dr. Feldmeyer /Dr. Kellner Hagen, Germany; 4Biometry and Statistics, Georg-August-University Göttingen, Göttingen, GermanyCorrespondence: Wolfram Windisch, Department of Pneumology, Cologne Merheim Hospital Kliniken der Stadt Köln gGmbH, Ostmerheimer Strasse 200, Cologne, North Rhine Westphalia, Germany, Email windischw@kliniken-koeln.deObjective: Health-related-quality-of-life is frequently reduced following intensive care treatment. Unwarranted or unwanted therapeutic interventions should be avoided at all costs. Since COPD patients are often faced with difficult decisions, an assessment was made of their desire for disease education. Our aim was to identify patients understanding of their disease and what their attitudes are towards different treatment options and whether this correlates to demographic factors.Methods: The COPD-Assessment-Test (CAT) was used to measure subjective disease burden. The COPD-Questionnaire (COPD-Q) was used to assess subjects’ own knowledge of their disease. In addition, a specifically designed questionnaire was used to assess patient’s subjective level of desire to be educated on COPD-specific topics. A multiple linear regression analysis was performed to identify the demographic factors associated with a greater desire for disease-specific information.Results: 127 patients (67.2± 8.8 years) were prospectively enrolled. Mean CAT score was 21.3± 8.9 (95% CI:1– 40). The desire for medical consultation was highly individual. In terms of vaccination, 31.5% of patients wished for more information while 34.6% wished for less. This also held true for information on long-term pharmacological therapy (29.1% vs 30.7%, respectively). Information on behaviour in case of emergencies as well as smoking cessation were wished for 38% and 42% of patients, respectively. Results of the COPD-Q showed that subjects were well-informed about specific topics (vaccination, etiology, emergency-inhaler) and less informed about long-term pharmacotherapy. In linear regression analyses, age (p=0.086), sex (p=0.906), education (p=0.833), health literacy (p=0.336) and burden of disease (p=0.296) did not influence patients´ desire for disease-specific information.Conclusion: Based on our cohort, COPD patients wish for more medical information related to behaviour in emergency situations and smoking cessation. The desire for education on disease-specific topics did not naturally correlate with demographic characteristics. The provision of medical information to patients remains a highly individualized and essential part of patient care.Trial Registration: German Clinical Trials Registry (DRKS00022109).Keywords: COPD, medical education, CAT-score, COPD-Q, advanced care planning